Comparação de armadilhas atrativas para captura de moscas de importância médico-veterinária e sanitária em aviário - Travaini, Matheus Marucio (Universidade Federal de São Carlos, 2022)
Cattle farming is an important agricultural activity in Brazil. Among the biggest problems faced in this activity are the flies of medical-veterinary interest, which cause great losses for the sector, interfering in the quality and productivity of cattle production, the study consists of controlling these flies, which is done by attracting a bait inside a trap, which captures them, for mass control. Thus, the objective of the present work was to evaluate the use of different attractive baits and traps to control flies in poultry production. For this, two traps and three attractive baits were evaluated, with the objective of composing commercial kits most used in the market (the most attractive trap), with one trap containing swine liver as an attractive bait, and the other commercial trap containing the attractive solution Target® and Papa-mosca®, separately in each treatment. The trap containing only water (control) was also installed. The traps were installed on the Jaboticabal (SP) campus of UNESP in November 2021 (first trial) and the experiment was repeated in January 2022 (second trial). Throughout the experiment, the weather conditions were monitored through the meteorological station of the UNESP/Jaboticabal campus. The experimental design was in randomized blocks, with 4 blocks and 1 replication each. The counting of flies captured in the traps was performed 15 days after the installation in the field. The data were submitted to analysis of variance and the means were compared by Tukey's test (5%). It was found that the trap containing swine liver as an attractive bait promoted the capture of the largest number of flies in both installation periods. In the first installation, the use of swine liver resulted in an increase of 337% in relation to flies captured by the Target ® attractant and 360% in relation to the Papa-mosca ®. In relation to the second installation, this increase was 339% and 379%, respectively. These results show the potential of using swine liver as an alternative to baits currently available on the market, expanding the range of strategies for the control of flies in animal production.
Comparison of atractive traps to capture flies of medical, veterinary and sanitary importance in poultry production
Keywords: |Produção animal; Iscas atrativas; Manejo integrado de pragas; Animal production; Attractive traps; Integrated pest management; CIENCIAS AGRARIAS::ZOOTECNIA